Scrutinising the Contribution of Textual and Visual Resources in Campaign Posters: An SF-MDA - Fauziyyah, Afifah; Marlina, Neni; Ruslan, Ruslan (Universitas Siliwangi, 2024)
This qualitative research aims to analyse the textual and visual resources used in four campaign posters to promote parents’ awareness of children’s language development and reveal the contributions of each semiotic resource in representing the messages in the selected posters. The research data were four campaign posters promoting parents’ awareness of children’s language development published by Worcestershire Speech & Language Therapy NHS Trust for the “We Need to Talk” Month campaign. The data was obtained from Worcestershire Speech & Language Therapy’s official Twitter account, @SLT_Worcs. The research design used in this research was Multimodal Content Analysis (Serafini & Reid, 2019). This research employed document analysis and purposive sampling techniques to collect the data. Then, the data were analysed using SF-MDA analytical tools: Halliday and Matthiessen’s ideational meaning of Systemic Functional Linguistics (2004) and Kress and van Leeuwen’s representational meaning of Visual Grammar (2006). The findings showed that the textual resources mostly have material processes, indicating that the NHS Trust is trying to invite the viewers to take action and work together to overcome the issue and raise the viewers’ awareness. Meanwhile, all of the visual resources have transactional reaction processes, which indicate that the NHS Trust is addressing the viewers directly (using a gaze) to respond and react to the represented participants’ (depicted in the posters) gaze to work together to overcome the issue being raised in the four selected campaign posters. Keywords: Campaign posters; parents’ awareness of children’s language development; Systemic Functional Multimodal Discourse Analysis; Systemic Functional Linguistics; Visual Grammar.